A graduate recital in wind conducting: literature selection, analysis and lesson plans - Brockmeier, Allen Paul (Kansas State University, 2007)
This document contains historical, theoretical and lesson plans of the selected literature for the Graduate Conducting Recital of Allen Brockmeier. The conducting recital was held in the auditorium of Wichita County High School in Leoti, Kansas, Tuesday, May 8, 2007 at 7:30 PM with performers from the Wichita County High School Concert Band. Selections included “Down a Country Lane,” by Aaron Copland, transcribed for band by Merlin Patterson; “Korean Folk Song Medley,” by James D. Ployhar; “Yellow Mountains,” by Jacob de Haan; and “The Washington Post,” by John Philp Sousa, edited by Frederick Fennell. Analytical methods are based upon the Blocher/Miles Unit Studies from the Teaching Music through Performance in Band Series along with the Tracz concept of macro-micro score analysis.
Keywords: Wind Band Conducting; Music (0413)